Five lessons in uncomplicated appendicitis: Can we remove the surgery?. (16th November 2017) - Read, Andrew; Xu, Jane; Adams, Susan; Karpelowsky, Jonathan
Abstract: Appendicectomy has remained the treatment of choice for appendicitis for over a century and is the most commonly performed emergency operation in children. However, emerging evidence suggests that appendicectomy may not always be necessary in uncomplicated appendicitis, with early paediatric trials demonstrating that antibiotic‐only therapy can be safe and effective. Further rigorously designed and appropriately powered studies are necessarily to establish the place of non‐operative management of uncomplicated appendicitis in the future.